Judge’s Considerations In Imposing A Decision On Divorce Lawsuit On Early Marriage Cases In Bengkulu - Jelinda Dwi Oktaviani; M. Darudin; Akhmad Muslih (Bengkoelen Justice : Jurnal Ilmu Hukum, 2022)
According to Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage, marriage is considered legitimate if both men and women are 19 years old. But in reality, in Bengkulu city there are still many early marriages that occurred and resulting in divorce. This study aims to analyze and to describe why divorce cases in minor couples in Bengkulu city are quite high, as well as to analyze and to describe the basis of judges' considerations in imposing a decision on divorce lawsuit in early age couples. The type of research used in this study was empirical legal research. In empirical legal research, the law is conceptualized as an empirical symptom that can be observed in real life. Based on the results of the study, it is known that the cause of divorce cases in early age couples in Bengkulu city is due to the emergence of various problems after marriage, such as increasing domestic violence rates, children's education rights that have not fully given by their parents, and stigma that must be borne by the children. These issues generally result in divorce on early age couples. In addition, the basis of the consideration of the Bengkulu Religious Court of Class IA in imposing a decision on divorce lawsuit in an early age couples has no difference with couples who is not married at an early age. There are three judges' decisions, namely the first is legal certainty. When divorce happened, the status becomes certain, namely the widow and widower. This status certainty allows a divorced couple to remarry later in the day. The second is justice. Justice is fair according to the judge if divorced. The third is the benefit. If the status is left unclear, there will be no benefit. It can even be a mudarah or another problem again in the future.